Importance of Early Diagnosis of Small Solid Ameloblastoma in the Mandibular Alveolar Region: Case Report - Sol, Izabella; Rodrigues, Cristóvão Marcondes de Castro; Meneses-Santos, Daniela; Morais, Jéssica Brenda Rodrigues Medeiros; Silva, Marcelo Caetano Parreira da; Silva, Cláudia Jordão (ARCHIVES OF HEALTH INVESTIGATION, 2025)
Commonly located in the posterior region of the mandible, solid ameloblastomas are often diagnosed in significant sizes due to their slow and asymptomatic growth. However, when in smaller dimensions, doubts or failures in the diagnosis may occur. The objective of this study is to report a clinical case of solid ameloblastoma in the posterior alveolar region of the mandible, with initial differential diagnosis hypotheses of periodontal lesion, lateral periodontal cyst, ameloblastoma and odontogenic keratocyst. After clinical and radiographic examination, new diagnostic hypotheses emerged due tumor characteristics. An incisional biopsy was chosen and the diagnosis of solid ameloblastoma was defined. The radiolucent lesions found in the jaws in smaller dimensions must be carefully evaluated, as aggressive pathologies and with growth potential can be diagnosed initially, reducing the morbidity caused by these when they reach considerable sizes.